2014
DOI: 10.1007/s11926-014-0412-0
|View full text |Cite
|
Sign up to set email alerts
|

Erdheim–Chester Disease

Abstract: Erdheim-Chester disease (ECD) is a rare (approximately 500 known cases worldwide), non-inherited, nonLangerhans form of histiocytosis of unknown origin, first described in 1930. It is characterized by xanthomatous or xanthogranulomatous infiltration of tissues by foamy histiocytes, "lipid-laden" macrophages, or histiocytes, surrounded by fibrosis. Diagnosis of ECD involves the analysis of histiocytes in tissue biopsies: these are typically foamy and CD68+ CD1a− in ECD, whereas in Langerhans cell histiocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
214
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(237 citation statements)
references
References 56 publications
(65 reference statements)
7
214
0
16
Order By: Relevance
“…14,17,18 Almost all studies have reported a strong male predominance, which also occurs in the above-mentioned series (75%). 18 By 2014, only 8 pediatric cases were reported in the medical literature.…”
Section: Postoperative Coursementioning
confidence: 67%
See 4 more Smart Citations
“…14,17,18 Almost all studies have reported a strong male predominance, which also occurs in the above-mentioned series (75%). 18 By 2014, only 8 pediatric cases were reported in the medical literature.…”
Section: Postoperative Coursementioning
confidence: 67%
“…14,17,18 Almost all studies have reported a strong male predominance, which also occurs in the above-mentioned series (75%). 18 By 2014, only 8 pediatric cases were reported in the medical literature. 17,20,29 For a long time, it remained unclear whether ECD was the histological manifestation of some kind of abnormal immune response or whether it was a neoplastic lesion.…”
Section: Postoperative Coursementioning
confidence: 67%
See 3 more Smart Citations